Motivasi berprestasi atlet bulutangkis di kabupaten tolitoli ditinjau dari dukungan sosial orang tua, teman, dan pelatih - Eiredania Rynewati Terok; Arthur Huwae (Universitas Riau, 2022)
ABSTRACTA badminton athlete can excel if he has the motivation to excel. However, some athletes, especially in Tolitoli Regency, still show a lack of motivation to excel. In improving the performance of an athlete, apart from having the motivation to excel, the need for good social support from parents, friends, and coaches. Therefore, this study aims to determine the achievement motivation of badminton athletes in Tolitoli Regency in terms of social support from parents, friends, and coaches. The type of method used is quantitative with a correlational design. The participants who were involved in this study were 42 badminton athletes in Tolitoli Regency, using the quota sampling technique. The scale used is the athlete's achievement motivation scale and the social support scale. Based on the product moment correlation test from Karl Pearson, it was found that there was a positive relationship between parental social support and athletes' achievement motivation. On the other hand, social peer support is not significantly related to athlete achievement. Likewise with the support of social coaches which are not significantly related to the athlete's achievement motivation.Copyright © The Author (s) 2022Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.